Basic Characteristics of Oligodendrogliomas: The Shohada-e Tajrish Hospital Experience (2008-2014) - Mahsa Ahadi; Afshin Moradi; Azadeh Rakhshan; Alireza Arefian; Mitra Rafizadeh; Hanieh Zham (Iranian Society of Pathology, 2017)
Background and Objectives: Gliomas are the most prevalent subgroup of primary brain tumors with a relatively high mortality. However, oligodendrogliomas have a better prognosis compared to other subtypes due to their sensitivity to chemotherapy. Considering the low incidence and the resulting lack of information about oligodendrogliomas, particularly in Iran, this study aimed at assessing their basic characteristics. Methods:In this descriptive retrospective study, patients with definite diagnosis of oligodendroglioma were identified by reviewing the archives of pathology reports at the department of pathology of Shohada-e Tajrish Hospital during years 2008 to 2014. Age, gender, location, and the grade of the tumor were extracted and entered to the SPSS statistical software for analysis. Results: A total of 182 patients, including 115 males (63.2%) and 67 females (36.8%), were included with a mean age of 38.5±13.36 years. Frontal lobe was involved in 53 patients (29.1%), parietal lobe in 31 (17.0%), temporal lobe in 22 (12.1%), frontoparietal area in 15 (8.2%), parieto-occipital area in 11 (6.0%), temporoparietal and frontotemporal areas each in 9 subjects (4.9%), occipital lobe in 5 (2.7%), and the brainstem in 4 (2.2%). Furthermore, 108 cases (59.3%) had grade-2 and the remaining74 patients (40.7%) had grade-3 anaplastic oligodendrogliomas. The mean age of subjects with brainstem oligodendrogliomas was significantly lower than the other patients (p=0.025). Conclusion: Oligodendrogliomas commonly effects the frontal lobe, followed by the parietal and temporal lobes. The mean age of subjects with brainstem lesions was significantly lower than other patients. Age, gender or location of the tumor did not independently predict a higher grade lesion.